A community-engaged model for promoting youth behavioral health equity: voices from Washington State’s Community Prevention and Wellness Initiative - Terral, Heather F.; Newburg, Jordan; Karimova, Konul; Cooper, Brittany R.; Shrestha, Gitanjali (Frontiers in Public Health, 2025)
IntroductionPreventing youth substance use is a public health priority and community coalitions show promise for reducing youth substance use. The Community Prevention and Wellness Initiative (CPWI) is an innovative community coalition model that uses data to direct prevention efforts and resources to the highest-need communities in Washington State to reduce youth behavioral health disparities. The Washington State Health Care Authority (HCA) leverages federal and state funding to support CPWI, which implements evidence-based programs in collaboration with community-based organizations and other partners. Despite the growing evidence supporting community coalitions’ utility in prevention and public health promotion, less is known regarding how they can advance health equity in their communities.MethodsIn 2022, we collaborated with HCA to interview 16 CPWI Coalition Coordinators about how they integrate health equity into their work. The second and third authors conducted interviews, which were transcribed professionally. Using a consensus building approach, the team conducted a thematic analysis of the transcripts.ResultsThree general themes emerged: (1) Context, (2) Facilitators, and (3) Barriers. Coalition context included knowledge about the community’s demographics and dynamics, community capacity and past coalition functioning, and history. Facilitators of health equity promotion were rooted in relationships and adapting processes to enable community engagement. Barriers to health equity work were most commonly systemic, such as lack of access to healthcare, or lack of community resources. In addition to these themes, Coalition Coordinators highlighted key support needs (e.g., increasing funding and training) and shared important lessons learned, emphasizing the importance of relationship-building, cultural humility, and community-centered approaches.DiscussionHealth equity efforts vary by community, shaped by local contexts and resources. Strong partnerships, community engagement, and trust were critical facilitators, while their absence hindered progress. Despite challenges, CPWI coalitions demonstrate resilience and creativity in addressing barriers. CPWI demonstrates a strong case as an innovative community-engaged model for promoting youth behavioral health equity.